A COMPARATIVE RESEARCH BETWEEN EXTROVERT AND INTROVERT PERSONALITY ON SPEAKING ACHIEVEMENT - Intan Nur Ahmar; Sugiyanta (Department of English Education, Universitas Panca Sakti Bekasi, 2021)
Speaking is a productive skill that can be immediately observed. The major goal of all English language teaching should be to provide learners with the ability to use English effectively and accurately to achieve better communication. However, some students still have difficulty in speaking, because of their different performance levels. They process information differently and there is a difference in personality (extrovert and introvert). This current research is to investigate whether there is a significant difference between introvert and extrovert students on their speaking achievement at Cambridge School of English. 23 students were selected as the sample and their personality type was determined by using Eysenck Personality Questionnaire and their speaking score from the speaking test. This research was quantitative approach; a non-experimental research design. The result of the research reveals that there is a different mean score between the extrovert and introvert students although the difference is slight, the mean score of the extrovert students is 74 and introvert students is 76.54. Meanwhile by collecting numerical data analyzed using SPSS 22, the result of the independent sample t-test shows that the t-table is higher than t-count (-1.360<t-table 1.721), therefore H0 is accepted and Ha is rejected. It means that there is no significant difference between extrovert and introvert students in speaking achievement.